2022
DOI: 10.3390/ijms232112723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn Ions’ Insertion in Pseudo-Tetragonal Phased CaBi4Ti4O15-Based Ceramics for Highly Efficient Energy Storage Devices and High-Temperature Piezoelectric Applications

Abstract: In the present era of advanced technology, the surge for suitable multifunctional materials capable of operating above 300 °C has increased for the utilization of high-temperature piezoelectric devices. For this purpose, a pseudo-tetragonal phased CaBi4Ti3.98 (Nb0.5Fe0.5)0.02O15:xwt%MnO2 (CBTNF:xMn), with x = 0–0.20, ceramic system has been engineered for the investigation of structural, ferroelectric, dielectric and high-temperature-dependent piezoelectric properties. XRD analysis confirms that low-content Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Maximum remnant polarization (P r ~52.11 µC/cm 2 ) and saturated polarization (P S ~58.4 µC/cm 2 ) were observed for the BFST:0.15Sm ceramic composition (Figure 4b), which are much improved over those of pure BFST ceramic (P r ~42 µC/cm 2 and P S ~44.55 µC/cm 2 ). From Figure 4b, it can be observed that for the BFST:0.20Sm ceramic composition, the polarization values (P r ~47.1 µC/cm 2 and P S ~55.6 µC/cm 2 ) have reduced; this reduction in the polarization values can be associated with the percolation threshold value [26,27]. Keeping the Sm-ion content below percolation threshold values, the Sm-ions incorporate the BFST host ceramics and adjust at the vacant lattice sites successfully, causing an improvement in the ferroelectric behavior till BFST:0.15Sm ceramics.…”
Section: Resultsmentioning
confidence: 93%
“…Maximum remnant polarization (P r ~52.11 µC/cm 2 ) and saturated polarization (P S ~58.4 µC/cm 2 ) were observed for the BFST:0.15Sm ceramic composition (Figure 4b), which are much improved over those of pure BFST ceramic (P r ~42 µC/cm 2 and P S ~44.55 µC/cm 2 ). From Figure 4b, it can be observed that for the BFST:0.20Sm ceramic composition, the polarization values (P r ~47.1 µC/cm 2 and P S ~55.6 µC/cm 2 ) have reduced; this reduction in the polarization values can be associated with the percolation threshold value [26,27]. Keeping the Sm-ion content below percolation threshold values, the Sm-ions incorporate the BFST host ceramics and adjust at the vacant lattice sites successfully, causing an improvement in the ferroelectric behavior till BFST:0.15Sm ceramics.…”
Section: Resultsmentioning
confidence: 93%
“…Dielectric ceramic energy storage capacitors have become integral components in integrated circuits, aerospace, and other sectors. This could be attributed to their ability to operate at high voltages, ease of miniaturization, cost-effectiveness, and inherent safety measures . With the technological development and progress, the energy storage capacity of ceramic capacitors puts forward higher requirements, and therefore, it is necessary to improve the energy storage capacity of ceramic capacitors to make them meet requirements .…”
Section: Introductionmentioning
confidence: 99%